Development of integrated animation videos based on TPACK for improving mathematics learning outcomes - Suharmanto, Fajar; Hadi, Muhamad Sofian; Imawati, Sri (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: Indonesia has entered the fourth industrial revolution, marked by significant advances in computer technology and educational systems. The National Education System aims to create superior human resources by integrating advanced technological tools. This study aims to: 1) develop effective animated video media tailored for elementary school students; 2) evaluate the feasibility of the developed animated video media; and 3) analyze students' responses to the animated video learning media.Method: This research employed the Research and Development methodology, following the Dick and Carey instructional design model to systematically design, develop, and validate the instructional media. Data were collected through surveys, expert validation, and trials.Findings: The study revealed that integrating TPACK (Technological, Pedagogical, Content and Knowledge) into animated instructional videos effectively improves students' understanding of data processing concepts. Validation results showed high feasibility scores: 91% from material experts, 90% from media experts, and 95% from language experts. Field trials demonstrated a significant improvement in students' learning outcomes, with an average score increase of 15.2% from pre-test to post-test. Additionally, the videos successfully captured students’ interest and facilitated independent learning.Significance: This research contributes to the development of innovative, technology-integrated instructional media tailored to the needs of elementary students. The animated videos, compatible with various devices, address diverse learning styles and foster engagement. By merging content, pedagogy, and technology, this study supports the advancement of educational practices in the digital era and highlights the potential of TPACK-based media to enhance learning outcomes.